The effect of a marathon run on plasma and urine mineral and metal concentrations - Buchman, A. L.; Keen, C.; Commisso, J.; Killip, D.; Ou, C. N.; Rognerud, C. L.; Dennis, K.; Dunn, J. K. (Journal of the American College of Nutrition, 1998)
BACKGROUND: Little data exist on the requirements of trace metals and minerals for endurance athletes. Changes in body status of these elements must be examined before specific nutritional recommendations can be made. This study was designed to determine whether a marathon run was associated with changes in serum and urine metal and mineral concentrations. METHODS: Forty subjects who planned to complete the 1996 Houston-Tennaco marathon were recruited. Subjects had blood and urine samples collected 2 weeks prior to the race and immediately following the race. Blood and urine specimens were analyzed for copper, iron, magnesium and zinc concentrations. Blood was also analyzed for calcium concentration and ceruloplasmin activity. RESULTS: Twenty-six subjects (24 male, 2 female) completed the marathon. Finish times varied between 2 hours 43 minutes and 5 hours 28 minutes. There was no significant change in serum calcium, copper or zinc concentrations or ceruloplasmin activity. Serum and urine magnesium concentration decreased significantly (19.55+/-1.73 to 16.55+/-1.53 ppm, p=0.00001; 34.02+/-8.64 to 21.80+/-12.24 ppm, p=0.003, respectively). Serum iron concentration increased significantly (1.06+/-0.48 to 1.35+/-0.42 ppm, p=0.006), while urine copper and iron concentrations were below the limits of detection, zinc concentration did not change. CONCLUSIONS: Serum and urinary magnesium concentrations decrease during endurance running, consistent with the possibility of magnesium deficiency. This may be related to increased demand in skeletal muscle. Serum iron concentration increases, possibly related to tissue injury. The exact etiology for these observations, as well as their clinical significance, requires further investigation.